2018
DOI: 10.1111/gcb.14441
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gross primary production and evapotranspiration in juniper‐encroached grasslands

Abstract: Woody plant encroachment (WPE) into grasslands has been occurring globally and may be accelerated by climate change in the future. This land cover change is expected to alter the carbon and water cycles, but it remains uncertain how and to what extent the carbon and water cycles may change with WPE into grasslands under current climate. In this study, we examined the difference of vegetation indices (VIs), evapotranspiration (ET), gross primary production (GPP), and solar-induced chlorophyll fluorescence (SIF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 86 publications
(145 reference statements)
1
17
0
Order By: Relevance
“…Several satellite-based trials have reported the potential of far-red SIF to indicate drought and temperature stress at ecosystem scales (Berkelhammer et al, 2017;Koren et al, 2018;Song et al, 2018;Sun et al, 2015;Wang et al, 2018Wang et al, , 2016Wu et al, 2018;Yoshida et al, 2015;Zuromski et al, 2018). Others have used far-red SIF to monitor the dynamics of photosynthesis in the Amazon forest (e.g., Alden et al, 2016;Guan et al, 2015;Köhler et al, 2018b;Koren et al, 2018;Lee et al, 2013;Parazoo et al, 2013;Yang et al, 2018a), high-latitude forests (Jeong et al, 2017;Walther et al, 2016), tundra ecosystems (Luus et al, 2017;Walther et al, 2018), dryland ecosystems of southwestern North America (Smith et al, 2018;Zhang et al, 2016c), and across Australia (Ma et al, 2016;Sanders et al, 2016).…”
Section: Satellite-based Studiesmentioning
confidence: 99%
“…Several satellite-based trials have reported the potential of far-red SIF to indicate drought and temperature stress at ecosystem scales (Berkelhammer et al, 2017;Koren et al, 2018;Song et al, 2018;Sun et al, 2015;Wang et al, 2018Wang et al, , 2016Wu et al, 2018;Yoshida et al, 2015;Zuromski et al, 2018). Others have used far-red SIF to monitor the dynamics of photosynthesis in the Amazon forest (e.g., Alden et al, 2016;Guan et al, 2015;Köhler et al, 2018b;Koren et al, 2018;Lee et al, 2013;Parazoo et al, 2013;Yang et al, 2018a), high-latitude forests (Jeong et al, 2017;Walther et al, 2016), tundra ecosystems (Luus et al, 2017;Walther et al, 2018), dryland ecosystems of southwestern North America (Smith et al, 2018;Zhang et al, 2016c), and across Australia (Ma et al, 2016;Sanders et al, 2016).…”
Section: Satellite-based Studiesmentioning
confidence: 99%
“…Increasing fire frequencies are expected during the 21st century at mid to high latitudes, depending on the productivity in grassland and savanna communities (Moritz et al, 2012; Fusco et al, 2019). Juniper encroachment changes the carbon cycle and increases productivity in US grasslands (Wang et al, 2018), and thus it moves the grassland into a more fire‐prone state. When these ecosystems are dominated by fire‐sensitive species such as the non‐resprouters Ashe or common junipers ( Juniperus ashei , Juniperus communis ) (Fuhlendorf et al, 1997; Marozas et al, 2007), wildfire may cause marked changes in plant species composition due to complete dieback of formerly abundant woody species and an immediate decrease of shaded microhabitats (Ónodi et al, 2014; Kertész et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Counties with redcedar documented in the Great Plains and studies conducted in the Great Plains that document changes in the hydrology of the system as a result of redcedar encroachment. The majority of hydrological studies have employed experimental manipulations in locations where grasslands have undergone regime shifts to juniper woodland (e.g., Oklahoma) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Fewer studies have employed simulations or scenario analyses to assess the relative vulnerability of regions where grasslands are still intact, but at the early stages of redcedar encroachment (e.g., states in the Northern Great Plains), to delineate potential impacts to water resources with future spread and grassland conversion [39][40][41][42][43][44][45].…”
Section: Morphological and Physiological Traits Of Redcedarmentioning
confidence: 99%
“…Direct comparison of stand-level transpiration between grassland and redcedar is usually unavailable. For grassland, transpiration was mostly measured together with evaporation as evapotranspiration based on energy balance, remote sensing, or eddy flux techniques [28]. Partitioning evapotranspiration into transpiration and evaporation remains a formidable challenge in the tallgrass prairie [49].…”
Section: Transpirationmentioning
confidence: 99%